Immigration patterns inferred from oxygen isotope analysis of human teeth from the Tylos-period Maqaba burial mounds in Bahrain - Yu Itahashi; Kenji Okazaki; Kazuhisa Yoshimura; Yumiko Oyabu; Kiyohide Saito (Frontiers in Environmental Archaeology)
IntroductionThe aim of this study was to determine the geographic origin of human remains in the Maqaba burial mounds cluster dating from the Tylos period (approximately 330 BC to AD 300) in Bahrain, using stable oxygen isotope analysis of dental enamel from teeth found in the mounds. During the Tylos period, Bahrain was an important hub for trade routes between the Mediterranean, Mesopotamia, and India. Therefore, immigrants who traveled as merchants for cross-regional trade are possible candidates for the buried remains. In particular, we hypothesized that these tombs are occupied by Palmyrene settlers who migrated from Syria to Bahrain.MethodsTo test this hypothesis, we performed a detailed oxygen isotope analysis of dental enamel from skeletons in the mound to infer their geographic origins. Oxygen isotopic signatures of water from modern springs, wells, precipitation, and bottled water sourced from Bahraini wells were used as contemporary proxies for ancient oasis water, allowing a comparison to be made between enamel and water compositions.Results and discussionOur results indicate that many of the individuals interred in the Maqaba burial mounds cluster originated from higher latitudes than that of Bahrain, suggesting that they were immigrants who were involved in trade or administration, rather than native Bahrainis. Future studies are expected to provide more archaeological evidence that will clarify the exact origins of these immigrants.